Archaeological water histories of oman (ArWHO) project (2022-23): Iron age settlements and trade in yanqul wilayat - Harrower, Michael J.; Paulsen, Paige (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The ArWHO project’s 2023 season focused on the Iron Age and early Islamic Periods, specifically concentrating on mapping settlement architecture and exploring trade in softstone and copper resources in Yanqul Wilayat. The ArWHO team mapped architecture at four Iron Age sites, discovered an ancient softstone (chlorite) quarry, and tested an autonomous Ground Penetrating Radar system. Additionally, the project engaged local residents by organising a Yanqul Community Archaeology Day to share findings and promote awareness of archaeology. Our work clarifies the histories of ancient societies, their environment, architecture, and trade activities contributing to deeper understanding of the ancient past.
Keywords: Archéologie -- Oman